Spatio-temporal-functional assembly of Daqu microbiome: Mechanistic insights and quality improvement - Rui Ma; Xiaojie Nan; Yanting Li; Yuanyu Su; Mingxia Cheng; Yujie Zhang; Yang Cui; Qiong Zhou; Jingang Gu; Shang Guo (Food Research International, 2026)

Under greenhouse settings, mycorrhizal responsive herbs establish better in their own soil compared to less responsive counterparts - Stavros D. Veresoglou; Yang Liu; Jie Bai; Hanzhi Bao; Peipei Bao; Bolun Cai; Liqun Cai; Jiawei Cao; Chen Chen; Genrun Chen; Hongqiao Chen; Jiarong Chen; et al. (Plant and Soil, 2026)

Single atom anchored covalent organic framework assisted with machine learning for high-throughput pesticides discrimination - Rui Bai; Nan Chen; Chenchen Gong; Yanting Liu; Shasha Lu; Jianyu Yang; Qiulin Li; Yu Gu; Changming Li; Chunxian Guo (Chemical Engineering Journal, 2026)

Advancing the Understanding of Infilled Joint Shear Behavior: A Review of Modeling, Measurement, and Influential Factors - Leibo Song; Zhiyong Bai; Quan Jiang; Binghe Zhu; Gang Wang; Yanting Gu (Rock Mechanics and Rock Engineering, 2025)

Flexible, breathable and sweat-wicking pressure sensor for long-term monitoring of skin pressure - Juntong Zhu; Guoqing Yang; Xiaoru Dong; Ziyu Liu; Yanting Xu; Zongquan Gu; Zhuo Li (Chemical Engineering Journal, 2025)

A comparison of milk fat globule membranes and whey proteomes: New insight into variation nutrient differences between Buffalo, Cow, Goat, and Yak - Lu Chen; Tiannuo Hong; Ziqi Li; Guohui Shen; Yanting Gu; Juan Han (Food Chemistry, 2023)

Influences of tropical Pacific and North Atlantic SST anomalies on summer drought over Asia - Jianmin Zhang; Renguang Wu; Qinlu Gu; Xinhai Chen; Xiaojing Jia; Yanting Zhang (Climate Dynamics, 2023)

A Cross-Seasonal Linkage between Arctic Sea Ice and Eurasian Summertime Temperature Fluctuations - Yanting Liu; Yang Zhang; Sen Gu; Xiu-Qun Yang; Lujun Zhang (Advances in Atmospheric Sciences, 2023)

The status of the global food waste mitigation policies: experience and inspiration for China - Guohui Shen; Ziqi Li; Tiannuo Hong; Xin Ru; Kunzhen Wang; Yanting Gu; Juan Han; Yanzhi Guo (Environment, Development and Sustainability, 2023)
Food waste has become a significant challenge faced by the community with a shared future for mankind, and it has also caused a considerable impact on China's food security. Scholars across disciplines, international organizations, and especially policymakers are increasingly interested in food waste. Policies are seen as a powerful factor in reducing food waste, but current research on related policies is more scattered. This paper summarizes and analyzes the experiences of food waste policy development and implementation by systematically reviewing the studies on food waste reduction policies. The results of this paper's analysis show that current global food waste policies are focused at the national strategic level, with approaches such as legislation, food donation, waste recycling, awareness and education, and data collection. At the same time, we find that the current experience of developed countries in policy formulation and implementation is beneficial for policy formulation in developing countries. And taking China as an example, we believe that developing countries can improve food waste policies in the future by improving legislation, guiding the development of food banks, promoting social governance, and strengthening scientific research projects. These policies will all contribute strongly to global environmental friendliness. In addition, we discuss some of the factors that influence the development of food waste policies and argue that in the future, more consideration needs to be given to the effects of policy implementation and that case studies should focus more on developing countries. This will contribute to the global sustainable development process.

Anion-exchange assisted sequential deposition for stable and efficient FAPbI3-based perovskite solar cells - Xinning Jiao; Wei-Min Gu; Yanting Xu; Ke-Jian Jiang; Guanghui Yu; Qing-Wu Zhang; Cai-Yan Gao; Cai-Ming Liu; Xin-Heng Fan; Lian-Ming Yang; Yanlin Song (Chemical Engineering Journal, 2023)

Identification and association of novel lncRNA pouMU1 gene mutations with chicken performance traits - Tuanhui Ren; Yanting Zhou; Yu Zhou; Weihua Tian; Zhenzhen Gu; Song Zhao; Yadi Chen; Ruili Han; Xiaojun Liu; Xiangtao Kang; Zhuanjian Li (Journal of Genetics, 2017)